Increased Power Generation due to Exothermic Water Exsolution in CO2 Plume Geothermal (CPG) Power Plants. (November 2020) - Fleming, Mark R.; Adams, Benjamin M.; Kuehn, Thomas H.; Bielicki, Jeffrey M.; Saar, Martin O.
Highlights: H2 O in solution with CO2 is produced from the reservoir in CO2 geothermal systems. H2 O exothermically exsolves from solution as the fluid ascends in the vertical well. H2 O exsolution can increase the fluid temperature and pressure at the wellhead. H2 O solution mass fractions exceeding 2% require detailed solution density models. Higher surface temperatures can increase power generation despite liquid H2 O removal. Abstract: A direct CO2 -Plume Geothermal (CPG) system is a novel technology that uses captured and geologically stored CO2 as the subsurface working fluid in sedimentary basin reservoirs to extract geothermal energy. In such a CPG system, the CO2 that enters the production well is likely saturated with H2 O from the geothermal reservoir. However, direct CPG models thus far have only considered energy production via pure (i.e. dry) CO2 in the production well and its direct conversion in power generation equipment. Therefore, we analyze here, how the wellhead fluid pressure, temperature, liquid water fraction, and the resultant CPG turbine power output are impacted by the production of CO2 saturated with H2 O for reservoir depths ranging from 2.5 km to 5.0 km and geothermal temperature gradients between 20 °C/km and 50 °C/km. We demonstrate that the H2 O in solution is exothermically exsolved in the vertical well, increasing the fluid temperature relative to dry CO2, resulting in the production of liquid H2 O at the wellhead. The increased wellhead fluid temperature increases the turbine power output on average by 15% to 25% and up to a maximum of 41%, when the water enthalpy of exsolution is considered and the water is (conservatively) removed before the turbine, which decreases the fluid mass flow rate through the turbine and thus power output. We show that the enthalpy of exsolution and the CO2 -H2 O solution density are fundamental components in the calculation of CPG power generation and thus should not be neglected or substituted with the properties of dry CO2 .